Relação das condições de armazenamento com a qualidade fisiológica de sementes e composição do óleo extraído de cultivares de soja - Bordignon, Bruno Cesar Silva (2009)
The aim of this work was measure influence of parameters as environment conditions upon the seeds quality physiology and on aspects of oil quality extracted of soybean grains upon different storage conditions. For this the work had two experiments. The experiment one measured the quality physiology of soybean s seeds in levels the germination and vigor (accelerate aging and electric condutividy) with valuation initial, six and twelve months. The experiment had twelve treatment, with diferents combinations of temperature that varied of 25, 20, 10⁰C fix and regime of intermittence and air relative moisture high and low too in regime of intermittence, simulating the changes of weather conditions, during twelve months of storage. The experiment two had five treatments with temperature combinations of 20 and 10⁰C with air relative moisture, applied the fix form during the period the twelve months, utilized too two treatments with controlled atmosphere (CA), used the partial pressure of gases O2 1kPa and 0 kPa of CO2 and CO2 15kPa and 21 kPa of O2 maintain during the storage. The results for measures in experiment one was seeds exposed to high air moisture to shorts time period maintain the physiology potential of seeds, germination and vigor, the same of the initial, the better condition found in this work to storage of seeds was the 10⁰C with 74,1% air moisture, maintain the same initial quality in the 6 and 12 months, absent to cv. Miréia . The experiment two the measures of acidity index and peroxide showed that the combination of low temperature and air moisture were effectives in the grain conservation, to obtain oil.